Study of Equilibrium and Kinetics of Pb(II) in Solution Using Persimmon Tannin Gel as an Adsorbent - Thamrin Azis; La Ode Ahmad; Fajrin E. Rosa; Laode Abdul Kadir (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Heavy metals concentrations exceeding the recommended threshold are hazardous for the environment, so there is a need for handling it safely. The purpose of this research was to determine the adsorption capacity and kinetics of adsorption. This research uses an adsorption method in the process of removing Pb(II) heavy metal ions using persimmon tannin gel. Besides the influence of contact time, pH, and the concentration of Pb(II) metal ions on adsorption, a kinetics study was also carried out. The adsorption rate is obtained through the adsorption rate constant (K) and the reaction order generated from the kinetics model. Based on the results of the research, showed the optimum adsorption process, which is 20 minutes and at a pH of 5. The maximum adsorption capacity of 17.62 mg/g with the value of the standard energy changes of Gibbs adsorption (-ΔG° = -14.274 kJ/moll) indicates that the adsorption takes place through physical interaction. The kinetic adsorption gives the adsorption rates a constant of, k = 0.008231 g/mg.min.